STRATEGI GURU DALAM MENINGKATKAN PRESTASI BELAJAR DI UPTD SMPN 18 LAU MAROS - Raihannatul Jannah; Mustamin; Syarifa Raehana; Ahmad; Martini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the teaching methods applied by teachers in improving academic achievement of Islamic Religious Education (PAI) subjects of grade VIII students at SMP Negeri 18 Lau Maros. The aim is to reveal learning strategies, obstacles, and supporting factors for student success. Using a qualitative approach, data were collected through observation, in-depth interviews, and document review. Data were analyzed using data reduction, data presentation, and conclusion drawing methods. The research respondents consisted of PAI teachers and grade VIII students. The results of the study showed that teachers applied a teacher-centered and student-centered learning approach, and utilized various learning techniques such as lectures, group discussions, question and answer sessions, demonstrations, and various learning media. This method is designed to accommodate differences in student learning styles. Barriers to improving learning achievement include limited learning resources, the influence of students' social environment, and differences in academic ability between students. These differences in ability require inclusive and differentiated learning strategies. In contrast, support from parents, principals, and fellow teachers is a driving factor for success. This support creates a positive and conducive learning atmosphere. A fun and collaborative learning environment has been shown to improve student motivation and learning achievement. This study emphasizes the importance of comprehensive learning strategies and supportive learning environments in improving PAI learning achievement. As a suggestion for further research, it is necessary to explore more innovative and effective learning methods to overcome the identified obstacles.